Development of E-Module Ecosystem and Conservation Integrated Ethno-SETS Containing Merdeka Syntax to Increase Environmental Literacy - Maratul Matsna; Sudarmin Sudarmin; Andin Irsadi; Novi Ratna Dewi; Arif Widiyatmoko; Hun Ravy (Journal of Natural Science and Integration, 2025)
This research aims to determine the characteristics, feasibility and influence of using the Etno-SETS integrated module containing independent syntax on students' environmental literacy. This research method is R&D with the ADDIE type. The research sample used a non-probability technique with the type used being convenience sampling. The research instrument is an expert validation sheet from aspects of media, materials as well as integration and environmental literacy questions. Research data was analyzed using Aiken V to determine the feasibility of modules, t-test and N-Gain to determine the effect of using modules on environmental literacy. The research results show that the module on ecosystems and its conservation has the characteristics of presenting modules using links, presenting material on ecosystems and their preservation, presenting Etno-SETS content which is integrated with the Rumbio traditional restricted forest, using independent syntax learning flow, presenting learning videos and presenting interactive LKPD in the form of a barcode code. The results of the module feasibility assessment using Aiken’ V analysis using six raters obtained validity with valid criteria and the percentage of student responses with very good criteria. Modules have a significant influence on increasing students' environmental literacy as evidenced by the t-test value. Students' environmental literacy abilities increase with high category N-Gain scores. Thus, it is concluded that the Etno-SETS integrated ecosystem and conservation module containing Merdeka syntax can increase environmental literacy.Keywords: module, etno-SETS, environmental literacy, merdeka syntax